A Flexible Network Structure for Temperature Monitoring of a Super High Arch Dam. (6th November 2012) - Lin, Peng; Li, Qingbin; Hu, Hang
Abstract : The aim of the study presented in this paper is to develop a flexible network structure for temperature monitoring of a super high arch dam under construction period. The multiple channel temperature acquisition method collects and analyzes system including flexible and stable field bus for the sensors, communication between intelligent module and control unit is proposed. In this temperature monitoring system, a total of 3 kinds of networks which independently marked by ∗ (1), ∗ (2), and ∗ (3) were proposed, with ∗ (1) being the lowest priority and ∗ (3) being the highest priority. The lowest priority is field bus (ITU Bus) which connects all the grouped sensors into different channels of different intelligent acquisition modules. The ITU network protocol is a star type, and the network structure is independent on the sensors. The bus can connect different types of sensors such as strainmeter, stressmeter, jointmeter, rock-deformeter, piezometer et al., the measurement scope could be extended wider. This study provides a measuring technique has been successfully implemented in monitoring of the Xiluodu arch dam construction, and ultimately solved the shortcoming of manual measurement technique.